Pengaruh Pelayanan dan Kepuasan Terhadap Loyalitas Pengunjung pada Objek Wisata Permandian Air Panas Makula Kabupaten Tana Toraja - Bernike Friska Liling; Abedneigo Carter Rambulangi; Jens Batara Marewa (CV. Ulil Albab Corp, 2024)
This research aims to determine visitors' perceptions of service and its impact on their level of satisfaction and loyalty. This type of research is quantitative research. With data collection methods through observation, and questionnaires. The data analysis techniques used in this research are descriptive statistics and regression to identify factors that influence visitor satisfaction and loyalty. The results of this research show that factors such as service quality, price, cleanliness and facilities play an important role in determining the level of visitor satisfaction and loyalty. The practical implication of this research is the importance of tourist attractions continuing to improve service quality, in order to increase the satisfaction and loyalty of their visitors.